2010
DOI: 10.3748/wjg.v16.i28.3499
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia inducible factor-1α accumulation in steatotic liver preservation: Role of nitric oxide

Abstract: We found evidence for the role of the HIF-1alpha/NO system in fatty liver preservation, especially when IGL-1 solution is used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
59
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 50 publications
9
59
1
1
Order By: Relevance
“…Moreover, HIF-1a upregulation was associated with better preservation of steatotic and nonsteatotic liver grafts (Zaouali et al, 2010a). Our results show that HIF-1a and its target Epo mRNA expression were downregulated after cold ischemia reperfusion.…”
Section: Acetazolamide Protects Fatty Liver Against Ischemic Damagesupporting
confidence: 52%
See 1 more Smart Citation
“…Moreover, HIF-1a upregulation was associated with better preservation of steatotic and nonsteatotic liver grafts (Zaouali et al, 2010a). Our results show that HIF-1a and its target Epo mRNA expression were downregulated after cold ischemia reperfusion.…”
Section: Acetazolamide Protects Fatty Liver Against Ischemic Damagesupporting
confidence: 52%
“…HIF-1a is a key transcriptional factor mediating cellular adaptation under stress conditions, including IRI. Indeed, it plays an important role in fatty liver protection against cold IRI, and its protective action is related to its downstream proteins, including Epo and eNOS (Zaouali et al, 2010a;Eipel et al, 2012). Moreover, HIF-1a has been implicated in the AZ beneficial effects against renal IRI and in the case of acute mountain sickness ).…”
Section: Discussionmentioning
confidence: 99%
“…Five studies reported similar increases in nitrates/nitrites in both steatotic and lean livers post-IRI [69,[74][75][76][77] while the remaining 5 studies reported a greater increase in levels of nitrates/nitrites in steatotic livers post-IRI [46,57,65,66,72]. While the role of NO in the susceptibility of steatotic livers is still controversial, when a NO-inhibitor (L-NAME) was added to the preservation solution or given to the donor animal prior to surgery, hepatic function decreased more in steatotic livers post-IRI than in lean livers [57,74,76,77].…”
Section: Role Of Nitric Oxide In Steatotic Liversmentioning
confidence: 87%
“…Eight of the 63 studies reported HO-1 levels in steatotic livers. Four studies reported a greater increase in HO-1 levels in steatotic livers post-warm IRI [20,21,31,35] whereas in cold PRI, 2 studies showed similar increase in HO-1 levels in both types of liver [69,74] and another two studies showed decreased HO-1 protein levels in steatotic livers [60,76].…”
Section: Insulin-like Growth Factormentioning
confidence: 99%
See 1 more Smart Citation